1998
DOI: 10.1111/j.1744-7429.1998.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Seasonal Variation in the Richness of Ant‐Plant Interactions in México1

Abstract: The richness and seasonal variation of ant‐plant interactions were compared in four habitats in México: lowland tropical dry forest (La Mancha, Veracruz), coastal sand dune matorral (San Benito, Yucatán), semiarid highland vegetation (Zapotitlán, Puebla), and lower montane humid forest (Xalapa, Veracruz). The effects of temperature and precipitation on the seasonal distribution of the number of ant‐plant interactions differed among habitats. The general linear models fitted to the ant‐plant interaction curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 48 publications
3
79
2
3
Order By: Relevance
“…Vegetation structure alters food resources, nesting sites, and micro-climate conditions (Boomsma and Devries 1980;Rico-Gray et al 1998;Andersen et al 2006;Hoffmann and James 2011), and further regulates ant diversity, behavior, and interactions among species (Huxley and Cutler 1991; Botes et al 2006;Wilkinson and Feener 2007;Hill et al 2008). The general assumption is that species diversity is positively associated with vegetation complexity (Bonte et al 2002;Tews et al 2004;Sarty et al 2006).…”
Section: Ant Community and Vegetation Structurementioning
confidence: 99%
“…Vegetation structure alters food resources, nesting sites, and micro-climate conditions (Boomsma and Devries 1980;Rico-Gray et al 1998;Andersen et al 2006;Hoffmann and James 2011), and further regulates ant diversity, behavior, and interactions among species (Huxley and Cutler 1991; Botes et al 2006;Wilkinson and Feener 2007;Hill et al 2008). The general assumption is that species diversity is positively associated with vegetation complexity (Bonte et al 2002;Tews et al 2004;Sarty et al 2006).…”
Section: Ant Community and Vegetation Structurementioning
confidence: 99%
“…Several studies have reported correlations between the abundance of plants with extrafloral nectaries and ant abundance (Pemberton, 1998;Rico-Gray et al, 1998). Bentley (1977) and Rickson (1977) showed that plants may lose extrafloral nectaries in ecosystems void of mutualist ant species.…”
Section: The Need For More Field Datamentioning
confidence: 99%
“…In this area previous studies has been developed only for a few specific plant species, also studies at community level are scarce, and the available studies are centered on reproductive biology (Rico-Gray and Castro, 1996;García-Franco and Rico-Gray, 1997a;1997b;Arceo-Gómez et al, 2012), ant-plant interactions (Rico-Gray et al, 1998;Torres-Hernández -Hernández et al, 2000;Cuautle and Rico-Gray, 2003), diversity of ants by vegetation types (Rojas et al, 2014), floral visitors richness (González-Vanegas, 2011;Rodríguez-Morales et al, 2013), and frugivory by birds (Ortiz-Pulido, 1997). In addition, community-level studies have been developed for extrafloral-nectary bearing plants (Rico-Gray, 1993;Díaz-Castelazo et al, 2004;Rico-Gray et al, 2012), pollination networks (Hernández-Yáñez et al, 2013), and also studies on phenology (Castillo and Carabias, 1982;Mehltreter, 2006).…”
Section: Cristian Adrian Martínez-adriano Et Almentioning
confidence: 99%